2023
DOI: 10.1007/s00415-022-11551-8
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, health-related quality of life, and associated factors in Huntington’s disease: a systematic review

Abstract: Background Huntington’s disease (HD) is a genetic, neurodegenerative disease. Due to the progressive nature of HD and the absence of a cure, (health-related) quality of life ((HR)QoL) is an important topic. Several studies have investigated (HR)QoL in HD, yet a clear synthesis of the existing literature is lacking to date. We performed a systematic review on self-reported (HR)QoL, and factors and intervention effects associated with (HR)QoL in premanifest and manifest HD gene expansion carriers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Second, the study used self-reported data, which are subject to recall bias, particularly in terms of treatment-seeking behaviour and healthcare costs. Considering the nature of HD, some patients may present cognitive impairment that affects their ability to report accurate information [1]. Third, the cross-sectional design of the study does not allow for examination of changes over time or establishment of causality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the study used self-reported data, which are subject to recall bias, particularly in terms of treatment-seeking behaviour and healthcare costs. Considering the nature of HD, some patients may present cognitive impairment that affects their ability to report accurate information [1]. Third, the cross-sectional design of the study does not allow for examination of changes over time or establishment of causality.…”
Section: Discussionmentioning
confidence: 99%
“…Huntington’s disease (HD) is a rare, hereditary neurodegenerative disorder that profoundly impairs both physical and mental health, leading to disability and, ultimately, mortality [1]. The disease typically manifests in individuals between the ages of 30 and 50 years, with a median life expectancy of 15 years post-diagnosis [2, 3].…”
Section: Introductionmentioning
confidence: 99%
“…(2,4,5) Debido a la falta de tratamientos eficaces, la progresión gradual de la enfermedad y la necesidad continua de atención, la esperanza de vida de los pacientes es de entre 15 y 20 años tras la aparición de los síntomas motores. (6) Esta enfermedad no solo representa un desafío clínico debido a su complejidad neurodegenerativa, sino también genera una carga significativa en la calidad de vida de los pacientes y sus familias, afectando aspectos emocionales, sociales y económicos, además de generar un importante gasto de los recursos sanitarios, razón por la cual es necesario investigar nuevas alternativas de tratamiento, que contribuyan a su curación. (7) Siguiendo esta línea de investigación el uso de los oligonucleótidos antisentido (ASO ASO, por sus siglas en inglés ) se plantea como una opción terapéutica alentadora, ya que este tipo de medicamentos son diseñados para dirigirse específicamente donde existan mutaciones genéticas, modulando la expresión génica a través de diversos mecanismos, como la inhibición de la expresión de ARN mensajero, la modulación del empalme del ARN y la activación génica, permitiendo una regulación en la formación del gen anómalo, disminuyendo la acumulación de proteínas a nivel de las células nerviosas, frenando así la instauración y progresión de la enfermedad.…”
Section: Introductionunclassified
“…Due to the complex nature of HD and its impact on the quality of life (QoL) of both HDGECs ( 7 ) and their partners ( 8–10 ), there is a high need for multidisciplinary care services ( 11 , 12 ) especially in the light of the absence of a cure. Despite the emergence of HD expertise centers across Europe ( 2 , 13 , 14 ), access to these specialty care services is often impeded by the distance of centers ( 2 , 13 , 15 ), health care and transportation costs ( 2 , 13 ), or physical limitations in later stages of the disease ( 13 , 16 ).…”
Section: Introductionmentioning
confidence: 99%